27PThe prognostic value of neutrophil to lymphocyte ratio (NLR) and 18F-FDG PET SUV in breast cancer patients underwent neoadjuvant chemotherapy. (24th November 2019) - Bae, S J; Park, S; Cha, C; Lee, J; Kim, D; Ahn, S G; Jeong, J
Abstract: Background: There is growing evidence that elevated neutrophil to lymphocyte ratio (NLR) is associated with poor treatment response and survival outcomes in breast cancer. Also, standardized uptake value (SUV) of 18 F-fluorodeoxyglucose (FDG) PET has been applied as a prognostic factor in breast cancer. In this study, we investigated the treatment response and survival outcomes according to NLR and SUV in breast cancer patients who received neoadjuvant chemotherapy (NAC). Methods: Baseline NLR and SUVmax of 18 F-FDG PET was retrospectively analyzed in 273 breast cancer patients who were received NAC followed by surgery from January 2007 to June 2018. Baseline NLR is calculated as absolute neutrophil count divided by absolute lymphocyte count from blood samples taken before initiation of NAC. Of the total, 101 patients underwent 18 F-FDG PET after 3-4 cycles of NAC. The ΔSUVmax, the percentage reduction between SUVmax at baseline and after 3-4 cycles of NAC, was obtained from these patients. NLR and ΔSUVmax was classified as high and low relative to the median values (NLR: 2.04 and ΔSUVmax: 73.3%). Results: The patients with pathologic complete response (pCR) had lower NLR and higher ΔSUVmax. Among all patients, high NLR was associated poor survival outcomes in terms of disease-free survival (DFS, adjusted HR 2.42; 95% Cis, 1.23-4.78; P = 0.011) and overall survival (OS, adjusted HR 1.53; 95% Cis, 1.19-1.97; P = 0.001), respectively. In 101 patients with data for early change of SUVmax, the high NLR (adjusted HR 3.20; 95% CIs, 1.29-7.89; P = 0.015) and low ΔSUVmax (adjusted HR 3.20; 95% CIs, 1.29-7.89; P = 0.015) were an independent prognostic factor for poor RFS. When patients were categorized into four groups according to NLR and ΔSUVmax, the patients with high NLR and low ΔSUVmax had significantly poor RFS (adjusted HR 8.71; 95% CIs, 1.87-40.64; P = 0.006) compared to those with low NLR and high ΔSUVmax. Conclusions: Both the baseline NLR and ΔSUVmax were associated with treatment response and prognosis in breast cancer patients who received NAC. Moreover, we identified that metabolic non-responders with degraded immune system had a worst impact on survival outcomes. Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.